Socioeconomic disparities in physical health among Aboriginal and Torres Strait Islander children in Western Australia - Shepherd, Carrington; Li, Jianghong; Zubrick, Stephen (Routledge, 2012)
Objective. Few empirical studies have specifically examined the relationship between socio-economic status (SES) and health in Indigenous populations of Australia. We sought to provide insights into the nature of this relationship by examining socio-economic disparities in physical health outcomes among Aboriginal and Torres Strait Islander children in Western Australia. Design. We used a diverse set of health and SES indicators from a representative survey conducted in 2000-2002 on the health and development of 5289 Indigenous children aged 0-17 years in Western Australia. Analysis was conducted using multivariate logistic regression within a multilevel framework. Results. After controlling for age and sex, we found statistically significant socioeconomic disparities in health in almost half of the associations that were investigated, although the direction, shape and magnitude of associations differed. For ear infections, recurring chest infections and sensory function problems, the patterns were generally consistent with a positive socio-economic gradient - where better health was associated with higher SES. The reverse pattern was found for asthma, accidents and injuries, and oral health problems, although this was primarily observed for area-level SES indicators. Conclusion. Conventional notions of social position and class have some influence on the physical health of Indigenous children, although the diversity of results implies that there are other ways of conceptualising and measuring SES that are important for Indigenous populations. We need to consider factors that relate specifically to Indigenous circumstances and culture in the past and present day, and give more thought to how we measure social position in the Indigenous community, to gain a better understanding of the pathways from SES to Indigenous child health.